2017
DOI: 10.2134/itsrj2016.06.0508
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Arabidopsis DREB1A Gene in Transgenic Poa pratensis: Impacts on Osmotic Adjustment and Hormone Metabolism under Drought

Abstract: Drought stress is a major limiting factor in turfgrass management in many regions. The objective of this study was to examine responses of transgenic Kentucky bluegrass (Poa pratensis L.) overexpressing an Arabidopsis DREB1A gene to drought stress. Five transgenic Kentucky bluegrass (cv. Baron) lines overexpressing AtDREB1A and wild‐type (WT, nontransgenic plant) were subjected to water deficit for 12 d and then rewatering treatment for 3 d. Leaf relative water content (RWC), turf quality, electrolyte leakage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…Thus, the stressed plants have a lower copy number of the DREB1A gene and are therefore susceptible to water stress. This agrees with Xu et al (2017) on the overexpression of the DREB1A gene in transgenic Poa pratensis. DREB1A is an important elixir of the gene modulation system and may play a crucial role when a plant is under water-stress conditions.…”
Section: Gene Expression Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the stressed plants have a lower copy number of the DREB1A gene and are therefore susceptible to water stress. This agrees with Xu et al (2017) on the overexpression of the DREB1A gene in transgenic Poa pratensis. DREB1A is an important elixir of the gene modulation system and may play a crucial role when a plant is under water-stress conditions.…”
Section: Gene Expression Studiessupporting
confidence: 89%
“…Based on previous reports on the use of reference genes for studies in plant species (Brunner et al 2004, Zhang et al 2016, Yi et al 2022, for this study, we selected ACT1 as the standard. Two drought-related genes (DREB1A and P5CS) were used for the expression study (Xu et al 2017, Yang et al 2021. ACT1 encodes the single essential gene, the ubiquitous, conserved cytoskeletal element critical for many cellular processes.…”
Section: Selection Of Targeted and Reference Genes And Primer Designmentioning
confidence: 99%
“…Almost all of the candidate genes, such as transcriptional factor (TF) genes and biosynthetic enzyme genes, were positively regulating. When overexpressing an Arabidopsis DREB1A gene in Kentucky bluegrass, the transgenic plants showed higher drought tolerance than control [96]. Overexpression of the cytokinin synthesizing gene isopentenyl transferase in creeping bentgrass resulted in the regulation of expression of several TF genes including MYB, bHLH and WRKY, and drought tolerance was enhanced [97].…”
Section: Drought Stressmentioning
confidence: 99%
“…Rubisco, GAPDH, and Rubisco-activated enzymes are all involved in the recovery of photosynthetic rate to drought stress in P. pratensis . Moreover, Xu et al (2017b) overexpressed the AtDREB1A gene in P. pratensis and validated its role under drought stress. They found that increased drought resistance of transgenic grass may be associated with an increased accumulation of organic solutes (WSC, proline, and protein) and altered hormone metabolism.…”
Section: Current State Of Research On the Stress Tolerance Of Turfgra...mentioning
confidence: 87%